2014
DOI: 10.1111/jce.12464
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pacing Site on QRS Duration and Its Relationship to Hemodynamic Response in Cardiac Resynchronization Therapy for Congestive Heart Failure

Abstract: In our study, we have demonstrated that changes of QRSd during LV pacing correlated with acute hemodynamic response and that LV pacing location was a primary determinant of paced QRSd. Although QRSd did not predict the maximum hemodynamic response, our results confirm the link between electrical activation and hemodynamic response of the LV during CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Derval et al. (22) found that LVendo pacing was superior to posterolateral LVepi pacing in nonischemic patients with significant individual variation between the optimal LVendo pacing sites (22). Spragg et al.…”
Section: Discussionmentioning
confidence: 99%
“…Derval et al. (22) found that LVendo pacing was superior to posterolateral LVepi pacing in nonischemic patients with significant individual variation between the optimal LVendo pacing sites (22). Spragg et al.…”
Section: Discussionmentioning
confidence: 99%
“…6 Electric activation times (ATs) as measured by contact mapping were decreased with ENDO-CRT BV over EPI-CRT BV , consistent with concurrent improvements in systolic LV function and more synchronous electric activation compared with EPI-CRT BV . [8][9][10] Specifically, ENDO-CRT BV resulted in an average decrease in LV endocardial and BV epicardial latest ATs (LATs; measured as time from stimulus) of ≈16% and 11%, respectively, when compared with EPI-CRT BV at the equivalent transmural epicardial location. Similar improvements in electric synchrony have been reported for canines undergoing ENDO-CRT BV with LBBB and myocardial infarction, or LBBB with HF.…”
mentioning
confidence: 99%
“…Additionally, although QRS intervals were similar at baseline, MG had a significantly shorter QRS interval than controls at the 6-month follow-up, which is comparable with better cardiac synchrony in MG. A longer Q-LV interval and a shorter QRS interval have been reported to be a better prognostic parameter of CRT response. [16][17][18][19][20] Thus, the Q-LV interval in MG versus CG represents a better prognosis of the former in this study. In the SMART-AV study, Gold et al found that patients with a Q-LV greater than the median 95 milliseconds had better outcomes.…”
Section: Discussionmentioning
confidence: 56%